Association Between Nutritional Status and Age at Menarche - Harahap, Asrika Sari; Santosa, Heru; Siagian, Albiner (Journal of Maternal and Child Health, 2019)
Background: Menarche age is often considered for various reasons. It is one of the major indices of the female fertility which includes the period up to the menopause. More critically, menarche marks the onset of ovarian activity associated with reproduction and affects breast cancer risk. Some earlier studies reported that subjects who had menarche before 13 years of age were at a significantly higher risk of cancer cervix. Nutrition has an important bearing on age at menarche. Menarche is attained earlier by well-nourished adolescents. This study aimed to assess the relationship between menarche age and body mass index.Subjects and Method: This was a cross-sectional study conducted at Ki Hajar Dewantara Foundation Junior High School, Kota Pinang, Labuhanbatu Selatan, North Sumatera, in December 2017. A sample of 58 school girls attending Junior High School was selected for this study. The dependent variable was the menarche age. The independent variable was the body mass index (BMI). Body weight was measured by a scale. Body height was measured by micro toise. Other variables were measured by questionnaire. The data were analyzed by simple logistic regression.Results: BMI ≥ 25 was associated with an earlier menarche age (OR = 0.71; 95%CI= 0.20 to 0.85; p= 0.046).Conclusion: BMI ≥ 25 is associated with an earlier menarche age.Keywords: menarche age, body mass index, adolescentsCorrespondence: Asrika Sari. Masters Program in Public Health, Universitas Sumatera Utara, Jl. Universitas No.21, Medan 20115, North Sumatera, Indonesia, Email: asrikasariharahap1993@gmail.com. Mobile: +6282274134348.Journal of Maternal and Child Health (2019), 4(5): 335-337https://doi.org/10.26911/thejmch.2019.04.05.05